“What do you offer?“: Interlinkages of universities and high-technology companies in science and technology parks in Berlin and Seville - Sascha Brinkhoff; Lech Suwala; Elmar Kulke (Universities, Cities and Regions: Loci for Knowledge and Innovation Creation, 2012)
The innovation process is characterized by interactive learning involving multiple entities (Lundvall 1988). The flow and exchange of information and knowledge spurs R&D activities and innovation enhancing regions' economic growth and competitiveness. Being aware of this process, government policies aim to stimulate and even plan inter-organizational interaction (Ibert 2010; Hewitt-Dundas 2011). In this respect, science parks have become prominent instruments of government infrastructure support to promote business-to-science relationships based on geographical proximity. Universities as sources of knowledge play a major role in science parks and in regions in general. They primarily contribute to the regional economy's competitiveness and innovativeness by providing access to new scientitifc knowledge, developing solutions for specific problems and by offering access to skilled talent and equipment, as well as research techniques (Hewitt-Dundas 2011). The purpose of this chapter is to discuss the role of universities in two science parks in Berlin and Seville and their contribution to localized interactive innovation processes. Both case studies provide similarities in their development process, although, as we shall see later, distinct conceptual framework conditions regarding business-to-university linkages differ. In the case of science parks, the literature predominantly stresses the great significance of geographical proximity. In this chapter, however, we focus on the discussion of the multidimensional character of proximity – integrating `relational proximity' to the strict geographical interpretation of proximity. Thus, we aim to add further aspects to the `soft architecture of learning' (Thune 2009: 9) within the regional and science park-related network of university-industry-government relations (`Triple Helix') (Etzkowitz and Leydesdorff 2000: 109). Finally, we make some proposals for policy implications regarding how to more successfully stimulate business-to-university linkages and associated localized innovation processes in science parks in particular, as well as in regions.
https://doi.org/10.4324/9780203097144
Keywords: P25; R11; R58; O32; O36; O33; D83; 330; Science and Technology Parks; Regional Innovation Systems; Regional Development; Proximity; University-Industry-Government Relations; Triple Helix; Berlin; Seville